Consultation-Liaison psychiatric service delivery: results from a European study - Huyse, F (2012)
The reported findings of the European Consultation-Liaison Workgroup (ECLW) Collaborative Study describe consultation-liaison service delivery by 56 services from 11 European countries aggregated on a C-L service level. During the period of 1 year (1991), the participants applied a standardized, reliability tested method of patient data collection, and data were collected describing pertinent characteristics of the hospital, the C-L service, and the participating consultants. The consultation rate of 1% (median; 1.4% mean) underscores the discrepancy between epidemiology and the services delivered. The core function of C-L services in general hospitals is a quick, comprehensive emergency psychiatric function. Reasons to see patients were the following. deliberate self-harm (17%), substance abuse (7.2%), current psychiatric symptoms (38.6%), and unexplained physical complaints (18.6%) (all means). A significant number of patients are old and seriously ill. Mood disorders and organic mental disorders are most predominant (17.7%). Somatoform and dissociative disorders together constitute 7.5%. C-L services in European countries are mainly emergency psychiatric services and perform an important bridge function between primary, general health, and mental health care.